Pengembangan Media Video Animasi Berbasis Adobe Illustrator untuk Meningkatkan Hasil Belajar pada Materi Keberagaman dan Penghormatan terhadap Perbedaan Agama dan Budaya di Kelas VI SD Bright School Jakarta Selatan - Reza, Rendy; Sutisna, Mohamad; Subkhan, Muhamad (STAIN Bengkalis, 2025)
This study aims to develop and evaluate the feasibility of Adobe Illustrator-based animated video media for teaching diversity and respect for religious and cultural differences in Grade VI at Bright School, South Jakarta. The background of this research is rooted in the low effectiveness of conventional teaching methods, which predominantly rely on lectures and non-interactive media, causing students to struggle in fully understanding the concept of diversity. This research employed a Research and Development (R&D) method using a modified Borg & Gall model, consisting of needs analysis, design, development, expert validation, revision, and limited and wider trials. The subjects included 30 students, two subject matter experts, and two media experts. Research instruments comprised validation questionnaires, learning achievement tests (pre-test and post-test), and response questionnaires for both students and teachers. The validation results indicated that the media was deemed highly feasible, with an average score of 91%. Effectiveness testing revealed a significant improvement in students’ learning outcomes, from an average score of 60.4 (pre-test) to 83.1 (post-test), with an overall increase of 22.7%. Both students and teachers responded very positively, stating that the animation media was engaging, easy to understand, and motivating. It can be concluded that Adobe Illustrator-based animated video media is effective in enhancing students’ comprehension, tolerance, and respect for diversity, while serving as an innovative alternative for character-based learning in elementary schools.